2013
DOI: 10.1016/j.neurobiolaging.2013.03.023
|View full text |Cite
|
Sign up to set email alerts
|

Development of amyloid burden in African Green monkeys

Abstract: The vervet is an old world monkey increasingly being used as a model for human diseases. In addition to plaques and tangles, an additional hallmark of Alzheimer’s disease is damage to neurons that synthesize noradrenaline (NA). We characterized amyloid burden in the posterior temporal lobe of young and aged vervets, and compared that to changes in NA levels and astrocyte activation. Total Aβ40 and Aβ42 levels were increased in the aged group, as were numbers of amyloid plaques detected using antibody 6E10. Low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
29
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 54 publications
9
29
1
Order By: Relevance
“…Here, we found that reductions in global measures of brain size (such as cerebral volume and total brain surface area) were associated with reduced CSF Aβ 1–40 and elevated CSF p‐tau 181 . Taken together with previous observations of age‐related amyloid plaques in the vervet (Kalinin et al., ; Lemere et al., ), the relationships with Aβ 1–40 and p‐tau 181 are consistent with a scenario of age‐related accumulation of amyloid plaques (in parenchyma and/or vasculature) corresponding to cerebral atrophy in the vervet. Though previous studies have found limited phospho‐tau immunoreactivity and few neurofibrillary tangles in the vervet brain (Lemere et al., ), the fact that elevations in p‐tau 181 levels in CSF are also correlated with changes in brain morphometry suggest that tau pathology may also play a role.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Here, we found that reductions in global measures of brain size (such as cerebral volume and total brain surface area) were associated with reduced CSF Aβ 1–40 and elevated CSF p‐tau 181 . Taken together with previous observations of age‐related amyloid plaques in the vervet (Kalinin et al., ; Lemere et al., ), the relationships with Aβ 1–40 and p‐tau 181 are consistent with a scenario of age‐related accumulation of amyloid plaques (in parenchyma and/or vasculature) corresponding to cerebral atrophy in the vervet. Though previous studies have found limited phospho‐tau immunoreactivity and few neurofibrillary tangles in the vervet brain (Lemere et al., ), the fact that elevations in p‐tau 181 levels in CSF are also correlated with changes in brain morphometry suggest that tau pathology may also play a role.…”
Section: Discussionsupporting
confidence: 88%
“…Nonhuman primates, unlike most other model organisms (e.g. mice and rats), are known to develop age-related amyloid pathology similar to that of Alzheimer's disease (AD) in humans (Kalinin et al, 2013;Ndung'u et al, 2012;Podlisny, Tolan, & Selkoe, 1991;Rosen et al, 2008;Toledano, Álvarez, López-Rodríguez, Toledano-Díaz, & Fernández-Verdecia, 2014), and have complex behavioral phenotypes closer to that in humans than other species could achieve. AD-related genes, such as those encoding β-amyloid (Aβ, APP) and tau (MAPT), are also highly similar (Holzer, Craxton, Jakes, Arendt, & Goedert, 2004;Podlisny et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…A limited number of studies have also been done examining AD associated neuropathology in vervets. Vervets live to approximately 30 years in captivity and have evidence of Aβ deposition, gliosis and neuronal dystrophy with age [72, 88, 89]. Amyloid deposition is first observed at approximately 15 years, and appears first in the vasculature prior to parenchymal plaques.…”
Section: Physiological Modelsmentioning
confidence: 99%
“…Vervets are relatively abundant, are not carriers of Herpes B virus, are easy to handle, and are less expensive than macaques [Baulu et al, ; Jasinska et al, ]. Vervets have been used in a wide variety of research areas including brain imaging [Fears et al, ; Woods et al, ], obesity and diabetes [Cann et al, ; Kavanagh et al, ], Alzheimer's disease [Kalinin et al, ; Lemere et al, ]; pharmacology/cognition [Groman et al, ; James et al, ; Melega et al, , ], immunology [Pandrea et al, ; Zahn et al, ], and genetics [Freimer et al, ; Jasinska et al, , ; Voruganti et al, ].…”
Section: Introductionmentioning
confidence: 99%